STABILITY-INDICATING METHOD DEVELOPMENT AND VALIDATION FOR THE SIMULTANEOUS ESTIMATION OF ROSUVASTATIN CALCIUM AND CLOPIDOGREL BISULFATE IN PHARMACEUTICAL DOSAGE FORM BY REVERSE-PHASE HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY - PIMPALE, AWDHUT; KAKDE, RAJENDRA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The present work was focused on the development and validation of reversed-phase high-performance liquid chromatography (RP-HPLC) method which is simple, rapid, precise, accurate, sensitive, economical, and stability-indicating for the quantification of rosuvastatin (RSV) calcium and clopidogrel bisulfate (CLO) in bulk and tablet formulation. Methods: The separation was attained on RP Princeton (C18) column with dimensions (250 mm × 4.6 mm, 5 μ) employing buffer which is a mixture of water (pH 3.0, adjusted with orthophosphoric acid), and methanol in the ratio (20:80) v/v as mobile phase, at flow rate 1.0 ml/min and detection was carried out at wavelength 240 nm. The retention time under the optimized condition of RSV calcium and CLO was found to be 2.844 min and 4.388 min, respectively. Results: The linearity of the method was demonstrated in the concentration range of 6–16 µg/ml and 45–120 µg/ml for RSV calcium and CLO with a correlation coefficient (r2) of 0.9999 and 0.9996, respectively. The percentage relative standard deviation was ˂2% and percentage recovery was found to be 100.12–101.37% and 99.72–101.09% for RSV calcium and CLO, respectively. Assay of marketed tablet formulation was found to be 98.99% and 99.92%, respectively. Conclusion: The developed RP-HPLC method was found to be simple, specific, sensitive, rapid, linear, accurate, precise, and economical and could be used for regular quality control of RSV calcium and CLO in bulk and tablet formulations.